2019
DOI: 10.1016/j.beth.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Gains in Relationship and Individual Functioning Following the Online OurRelationship Program

Abstract: In the United States, more than 40% of marriages end in divorce and more than one third of intact marriages are distressed. Unfortunately, only a minority of couples seek couple therapy to improve their relationships. Online interventions, with their increased reach and reduced costs, offer the potential to improve relationships nationwide. The online OurRelationship program has been shown in previous nationwide studies to improve relationship and individual functioning. The present study examined whether init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 48 publications
(69 reference statements)
3
55
1
Order By: Relevance
“…OurRelationship may best be thought of as a hybrid between a therapy experience and relationship education, as the program focuses on an existing problem rather than preventing future problems. Couples participating in the intervention have reported gains in relationship satisfaction and confidence, reduced depressive symptoms, and improved quality of life (.18 < d < .69; Doss et al, ; Doss, Roddy, Nowlan, Rothman, & Christensen, ).…”
Section: Evidencementioning
confidence: 99%
“…OurRelationship may best be thought of as a hybrid between a therapy experience and relationship education, as the program focuses on an existing problem rather than preventing future problems. Couples participating in the intervention have reported gains in relationship satisfaction and confidence, reduced depressive symptoms, and improved quality of life (.18 < d < .69; Doss et al, ; Doss, Roddy, Nowlan, Rothman, & Christensen, ).…”
Section: Evidencementioning
confidence: 99%
“…Most relevant to the present study, initial findings on the maintenance of initial gains from online couples’ programs are also encouraging. Couples in an initial trial of OR in a sample of socioeconomically diverse couples reported maintenance of relationship and individual gains through 12 months postintervention and even continued to improve in positive relationship quality and anxiety over follow‐up (Doss, Roddy, Nowlan, Rothman, & Christensen, 2019). Previous work on ePREP has also found reductions in physical and psychological aggression one year after the intervention (Braithwaite & Fincham, 2014).…”
Section: Current Studymentioning
confidence: 99%
“…In addition, if control‐group participants are offered the intervention soon after treatment‐group participants have finished the program, then observing long‐term differences between treatment and control groups is not possible. (To compensate, some researchers track treatment‐group changes from the immediate posttreatment assessment to examine whether initial changes are maintained; see Doss, Roddy, Nowlan, Rothman, & Christensen, ).…”
Section: Fle Program Evaluation Best Practicesmentioning
confidence: 99%